UPAYA PENANGGULANGAN PENYALAHGUNAAN NARKOBA OLEH KEPOLISIAN (STUDI KASUS SATUAN NARKOBA POLRES METRO BEKASI) - Paul Ricardo (Jurnal Kriminologi Indonesia, 2010)
The large number of illegal drugs use in the society was because the drugs trade still rising. The city of Bekasi has become a market for drug trade. The large number of cases can be seen through cases that being handled by the Bekasi Police Metropolitan Resort Anti Drug Unit. This study was exploring every aspect on how the Bekasi Police Metropolitan Resort Anti Drug Unit handles the drug problem which threatens the city of Bekasi. The Bekasi Police Anti Drug Unit handles the drug problem on its jurisdiction in three important efforts. The pre-emptive done as early as possible in form of informal seminar and local counseling to the society about the dangerous effect of illegal drug use. The preventive effort was implementing through series of Routine Police Operation and Special Police Operation. While the repressive efforts were law enforcement action through criminal investigation and indictment which rooted within legality aspect. Each effort still encounters several problems, such as lack of personnel, insufficient equipment, breach of information and lack of operational funds.